Uncertainty and the limits of markets - Roni Hirsch (Duke University, Center for the History of Political Economy (CHOPE), 2020)
The article considers the place of the neoclassical equilibrium model as the basis for current views of markets as fair, efficient, or both. It also points to three threats the model poses for democracy and justice: it ignores the problem of inequality, it suppresses the socio-economic significance of uncertainty, and it conceals its own tradeoff between certainty and equality. Instead, the article lays out Frank Knight's critical assessment of real markets, which rely on the tacit agreement between a handful of "daring" entrepreneurs and the "risk-averse" masses to bear the uncertainties of business-life in return for a substantially larger share of its direction and rewards. Knight's influential conclusion, that this agreement mandates a nonmeritocratic social inequality and substantively divides humanity into leaders and followers, should be critically examined.
Keywords: 330; Frank Knight; inequality; uncertainty